(untitled) (Bulletin of criminological association of Ukraine, 2023)
It was found that under the subject of ensuring international cooperation, it is most appropriate to understand specially authorized state and non-state institutions that are endowed with a special set of subjective rights and legal obligations, which give them the opportunity to enter into legal relations that arise due to the creation of conditions and organization of actual implementation of effective international cooperation in the field of physical culture and sports. It was concluded that the subjects of international cooperation in the field of physical culture and sports are not limited to the Ministry of Youth and Sports of Ukraine, but include a number of state institutions and organizations, each of which has its own special legal status, in particular: 1) Verkhovna Rada of Ukraine; 2) Cabinet of Ministers of Ukraine; 3) Ministry of Youth and Sports of Ukraine; 4) National Anti-Doping Control Laboratory. Today, in our opinion, it is important to create all the necessary conditions in order to ensure the appropriate level of interaction in this field between the outlined subjects, which, as it is seen, will allow: first, to create an appropriate regulatory and legal basis for international cooperation in the field of physical culture and sports; secondly, to ensure stability and consistency of state policy in the researched area.